2019
DOI: 10.1155/2019/9724214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Nitrification Inhibitor 3,4-Dimethylpyrazole Phosphate on the Deep Placement of Nitrogen Fertilizers for Soybean Cultivation

Abstract: The deep placement of urea fertilizer (DMU) containing 1% (W/W) of the nitrification inhibitor 3,4-dimethylpyrazole phosphate (DMPP) on soybean growth and seed yield was as effective as those of the coated urea (CU) and lime nitrogen (LN) in a field research. The average seed yields were high in LN (464 g·m−2) and DMU (461 g·m−2) and relatively low in CU (405 g·m−2), U (396 g·m−2), and Cont (373 g·m−2) treatments. The accumulations of dry matter and nitrogen in soybean shoots were higher in the plants with dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The DCD has been investigated for over 80 years for its outstanding nitrification inhibitory properties in agricultural soils (Zhang et al, 2015, Hatano et al, 2019. The outcomes of this experiment agreed with the results of De Klein and Eckard (2008), and Malla et al (2005), who reported reductions in direct N 2 O release from animal urine, livestock slurry, and urea along with DCD in the soil.…”
Section: Duringsupporting
confidence: 80%
See 1 more Smart Citation
“…The DCD has been investigated for over 80 years for its outstanding nitrification inhibitory properties in agricultural soils (Zhang et al, 2015, Hatano et al, 2019. The outcomes of this experiment agreed with the results of De Klein and Eckard (2008), and Malla et al (2005), who reported reductions in direct N 2 O release from animal urine, livestock slurry, and urea along with DCD in the soil.…”
Section: Duringsupporting
confidence: 80%
“…The powder of pomegranate fruit (PFP) can reduce urea breakdown (Al-Sabahi et al, 2017). Dicyandiamide, a strong synthetic nitrification inhibitor used with solid urea is produced and marketed in Japan and Germany (Hatano et al, 2019), which has been reported to reduce gaseous emissions significantly from the urea fertilized fields (Deklein et al, 2011;Zhang et al, 2015). But some issues are linked with the use of DCD, i.e., its high cost, availability, and toxicity (Byrne et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Using machinery, fertilizers were inserted deeply into the soil using this technique. [44] discovered that, in comparison to conventional fertilization, the deep placement method of applying lime nitrogen (LN) and urea fertilizer (DPF) increased the amount of nitrogen accumulated in soybean plants. As the plants developed, nitrogen fixation-a crucial mechanism for plant growth-improved, particularly with the deep application of slow-release lime nitrogen (LN) and urea fertilizer (DPF).…”
Section: Discussionmentioning
confidence: 99%
“…Interactions among SNF, N fertilizer, field history, management, and environmental conditions affect the contribution of exogenous N to soybean yield (Ciampitti and Salvagiotti, 2018;dos Santos Cordeiro and Echer, 2019). It should be noted that soybean response to N fertilization is quite complex, and a wide range of studies has investigated this topic, as crop phenology, timing, and rate of fertilizer application can modulate the results (de Oliveira et al, 2019;Hatano et al, 2019;Pierozan Junior et al, 2020;Santachiara et al, 2019). Nonetheless, it is not clear how much of the N applied is efficiently absorbed by the plant, especially whether CRFs enhance fertilizer recovery and plant N content compared to common fertilizers.…”
Section: Introductionmentioning
confidence: 99%